Cardiometabolic Disorders in the Offspring of Parents With Severe Mental Illness - Protsenko Maria; Kerkelä Martta; Miettunen Jouko; Auvinen Juha; Järvelin Marjo-Riitta; Jones Peter B; Gissler Mika; Veijola Juha (Lippincott Williams & Wilkins, 2022)
Objective: The elevated prevalence of cardiometabolic disorders is consistently reported in patients with severe mental illness (SMI). We explored the association between parental SMI and offspring cardiometabolic morbidity. Our hypothesis was that offspring of people with SMI have increased morbidity risk.
Method: The Northern Finland Birth Cohort 1966 is a study of offspring whose date of birth was expected in 1966. The follow-up lasted until 2015 (49 years). The final study sample included 11,175 children. We used parental SMI as the exposure in the study. The following cardiometabolic disorders were used as outcome measures: diabetes mellitus, hypertension, hyperlipidemia, coronary artery disease, obesity, and cerebrovascular disorders.
Results: There were 139 (14.7%; hazard ratios [HR] = 1.63; 95% confidence interval [CI] = 1.36-1.94) children of parents with SMI who developed cardiometabolic disorder during follow-up and 957 (9.4%) in the comparison cohort. Statistically significant HRs were found in males (HR = 1.95; 95% CI =1.56-2.44), but not in females (HR = 1.29; 95% CI = 0.96-1.73).
Conclusions: Having a cardiometabolic disorder was associated with male offspring of parents with SMI. Our findings suggest that there is an elevated risk of coronary artery disease, hyperlipidemia, obesity, and hypertension in the male offspring of parents with SMI. Our results suggest that the somatic health of offspring of parents with SMI should also be considered in addition to their mental health in clinical practice.